(untitled) (American Journal of Aquaculture and Animal Science, 2022)
Atlantic salmon (Salmo salar L) is the major important species in salmonid families. But for the disease issue, farmers are losing a large number of fish and income. Melanin in fillet is one cause for the loss of the processing industries. The cause of melanin spot are related to the use of vaccines containing oil adjuvants (Fagerland et al., 2013), but other factors such as environmental conditions, genetics and diseases (Bjerkeng, 2000) also appear to play a role. The pigmentary and the immune systems are related each other. Larsen et al. (2012) reported that the melanogenesis occurs in muscle-located granulomas, which represents an association between the immune and pigmentary systems. Melanin spot in fish fillet or organs create many problems to farmers and processing industries. Consumers do not prefer spotted fillet so processing industries need to cut off the defected part of the fillet, as a result, they face some loss in their product production. Addition of Vitamin C, E and selenium in feed can contribute to reduce the number and size of the melanin spot (Wang, 2016).